Sectoral co-integration and portfolio diversification benefits: a business cycle examination of South African equity sectors - Hofisi, Tinashe S (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2020)
The onset of globalisation and simultaneous changes in financial technology and financial reforms dissipated hurdles once faced in financial transactions among stock markets. Hence, stock markets around the world became increasingly integrated because there was a free flow of cross border investments. Consequently, international diversification diminished thereby undermining the ability of investors to diversify investments across borders. For that reason, recent literature on portfolio diversification is urging investors to shift their focus to domestic portfolio diversification as an alternative. On that account, this study aims to examine the co-integration and dynamic causalities between South African equity market sectors in order to ascertain the sectoral diversification opportunities available to domestic investors over time. The study was examined over the different phases of the business cycle as well as the full sample, i.e. 2004 "“ 2018, with a view to shedding light on the inter-sectoral diversification opportunities of domestic investors over the South African business cycle. The phases of the business cycle applied are a

expansion and boom; b

recession and recovery phase and c

stagnation phase. The Johansen co-integration and Granger-causality tests were employed. The hypothesis of the study is that, if sectors are not cointegrated, then diversification benefits can be reaped by constructing a portfolio that combines stocks from the respective sectors. On the whole, the findings of this study show that there are both long-run and short-run diversification opportunities across the different phases of the South African business cycle as well as the full sample. However, there are lesser diversification opportunities in the recession and recovery phase over both the long-run and short-run. These results indicate that domestic sectoral portfolio diversification is least effective when it is needed the most (i.e. in a period of heightened volatility such as recession and recovery phase). This study will contribute to the existing literature in two ways; firstly, to investors who intend to diversify their portfolios domestically rather than internationally and, secondly, after reasonably thorough research it was evident that there is scant literature on domestic sectoral diversification in South Africa. As a result, the study attempts to address this gap. Additionally, the essence of the business cycle in this study is to make investors aware of potential diversification opportunities when positioning their portfolios for the next shift in the business cycle.
Keywords: Portfolio management -- South Africa; Investments -- South Africa; Investments, -- South African; Stocks -- South Africa